Tense, aspect, modality, and evidentiality crosslinguistic perspectives - Ayoun, Dalila, 1963-; Celle, Agnès; Lansari, Laure (Studies in language companion series (SLCS),, 2018)
"After an introductory chapter that provides an overview to theoretical issues in tense, aspect, modality and evidentiality, this volume presents a variety of original contributions that are firmly empirically-grounded based on elicited or corpus data, while adopting different theoretical frameworks. Thus, some chapters rely on large diachronic corpora and provide new qualitative insight on the evolution of TAM systems through quantitative methods, while others carry out a collostructional analysis of past-tensed verbs using inferential statistics to explore the lexical grammar of verbs. A common goal is to uncover semantic regularities and variation in the TAM systems of the languages under study by taking a close look at context. Such a fine-grained approach contributes to our understanding of the TAM systems from a typological perspective. The focus on well-known Indo-European languages (e.g. French, German, English, Spanish), but also on less commonly studied languages (e.g. Hungarian, Estonian, Avar, Andi, Tagalog) provides a valuable cross-linguistic perspective"--